The Consequences of Policy Uncertainty : Disconnects and Dilutions in the South African Real Effective Exchange Rate-Export Relationship - Hlatshwayo, Sandile (IMF Working Papers; Working Paper ;, 2016)
In recent years, the link between the real effective exchange rate (REER) and exports in South Africa has weakened. While exports still rise in response to REER depreciations, the REER-export elasticity is below historical estimates. The literature has put forward a number of possible explanations, from multi-national supply-chains to muted exchange rate pass-through. This research explores the role of policy uncertainty in reducing the responsiveness of exports to relative price changes. We construct a novel 'news chatter' measure of policy uncertainty and examine how it, paired with other supply-side constraints, can improve our understanding of export performance. We find that increased policy uncertainty diminishes the responsiveness of exports to the REER and has short and long-run level effects on export performance. Finally, we show that a measure of competitiveness that adjusts for uncertainty and supply-side constraints greatly outperforms the REER in tracking exports performance.